2014
DOI: 10.15207/jkcs.2014.5.4.061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 8 Weeks of Schroth Exercise (Three-dimensional Convergence Exercise) on Pulmonary Function, Cobb's Angle, and Erector Spinae Muscle Activity in Idiopathic Scoliosis

Abstract: In the present study, we aimed to examine the effects of Schroth exercise(three-dimensional convergence exercise) on pulmonary function(vital capacity, and chest expansion), Cobb's angle, scoliometer angle, and erector spinae muscle activity. We examined 40 students with idiopathic scoliosis(Cobb's angle 10°). They were divided into the Schroth and conventional exercise groups, with 20 people in each group. Statistical analysis was performed by using SPSS 18.0 with a paired t-test(pre-post difference) and an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This suggests that improvement of the lordotic curve in the lumbar region after exercise intervention contributes to a decrease in the overload on the lumbar vertebrae and increases the lumbar muscle activity, resulting in an increase in the CSA of the lumbar muscles. This mechanism is supported by previous studies reporting the positive effects of the Schroth and mobilization exercises on muscle activity [19,23]. Further study is needed to confirm whether corrective exercise or resistance exercise would be more beneficial in terms of an increase in the CSA of the lumbar muscle in patients with FBS.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This suggests that improvement of the lordotic curve in the lumbar region after exercise intervention contributes to a decrease in the overload on the lumbar vertebrae and increases the lumbar muscle activity, resulting in an increase in the CSA of the lumbar muscles. This mechanism is supported by previous studies reporting the positive effects of the Schroth and mobilization exercises on muscle activity [19,23]. Further study is needed to confirm whether corrective exercise or resistance exercise would be more beneficial in terms of an increase in the CSA of the lumbar muscle in patients with FBS.…”
Section: Discussionsupporting
confidence: 74%
“…The deep lumbar muscles play an important role in maintaining control and stability of the spinal column [19]. The presence of a flat back is associated with malalignment in the spine, which could cause dysfunction of the deep lumbar muscles and result in chronic low back pain and deep muscle atrophy [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this is that the decreased thoracic kyphosis contributes to reduce the overload at the cervical vertebrae and to increase cervical muscle activity, resulting in improvement of CSA in the cervical deep muscles. This mechanism can be explained on the basis of previous studies reporting the positive effects of Schroth and mobilization exercise on muscle activity 14 , 15 . We suggest that combined corrective exercise should be considered as a more efficient exercise type for increasing CSA of cervical muscles, compared with traditional resistance exercise.…”
Section: Discussionmentioning
confidence: 82%
“…The corrective exercise applied in this study was an integrated exercise program and included mobilization exercise and Schroth method, while resistance exercise only included weight training. Mobilization exercise and the Schroth method can reduce the angle of thoracic hyperkyphosis 7 , 13 15 . Foad et al 11 reported that corrective exercise is a more effective intervention than a general exercise program for patients with thoracic hyperkyphosis which supports the present findings.…”
Section: Discussionmentioning
confidence: 99%
“…Among previous studies, those on the functional improvements proposed significant outcomes from Schroth Therapeutic Exercise in increase of CA and lung capacity [9] and decrease of low back pain [10]. However, studies on quantitative measurement and changes in external aspects like body surface area and volume, which are hardly observed physically in the treatment of scoliosis patients, have been so insufficient that our study was set out.…”
Section: Original Articlementioning
confidence: 97%